Ethnomathematics Exploration of The Masjid Raya Bandung Ornaments in Transformation Geometry Materials - Tia Purniati; Turmudi Turmudi; Dadang Juandi; Didi Suhaedi (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The mosque is the result of acculturation between Islamic culture and local culture. Many mosque ornaments use geometric motifs. This research is an ethnomathematics study that aims to explore the ethnomathematics aspects of mosque ornament, especially the material of geometric transformation Ethnomathematics research is part of qualitative research, so this research uses qualitative research. The purpose of ethnomathematics research is to study the mathematical ideas contained in a culture, so the method used is ethnographic. The research location is Masjid Raya Bandung which was selected by purposive sampling. The researcher acts as an instrument that collects data through observation, documentation, and literature review. The research data were analyzed through data condensation, data display, and concluding. The results showed that there are ethnomathematics aspects of Masjid Raya Bandung ornaments in the material of transformation geometry, namely translation, reflection, rotation, and dilation. The mosque ornaments can be used as an alternative source of learning in mathematics learning, especially transformation geometry material. Keywords: ethnomathematics, transformation geometry, mosque ornament.